Tinjauan Yuridis Tidak Diterimanya Gugatan Terhadap Perkara Sengketa Tanah - Rizki Jan Saputra Surbakti; Agus Salim Daulay; Sri Hidayani (Universitas Medan Area, 2021)
The dispute resolution mechanism referred to is in the form of a justice system. The court in question is the implementation of the law in terms of concrete demands for rights, which functions are carried out by an independent body and held by the state and are free from any influence whatsoever and by giving binding decisions. The factors that cause civil lawsuits to be rejected at the District Court are the arguments of the claim or fundamentals of the petitioner, do not have a clear legal basis. A lawsuit is considered vague if the argument of the lawsuit does not explain the legal basis and the event behind the suit. The object of the dispute is unclear, the location of the land is not mentioned. There are no equal borders, the lawsuit is unclear, the lawsuit is premature and the lawsuit has expired. In Decision No. 372 / Pdt.G / 2014 / PN.Mdn The Plaintiff feels disadvantaged by the Defendant, but in this case the arguments of the plaintiff's claim are groundless and groundless. Judges' basic considerations in deciding civil case No. 372 / Pdt.G / 2014 / PN.Mdn the object of the lawsuit that is still being examined in another case (Litispendentie exceptie), which is an object in a civil dispute in this case which is the reason for the plaintiff to file alawsuit.